Practical 3D Printers The Science and Art of 3D Printing - Evans, Brian. (Apress : Imprint: Apress, 2012)
Desktop or DIY 3D printers are devices you can either buy preassembled as a kit, or build from a collection of parts to design and print physical objects including replacement household parts, custom toys, and even art, science, or engineering projects. Maybe you have one, or maybe you're thinking about buying or building one.  Practical 3D Printers takes you beyond how to build a 3D printer, to calibrating, customizing, and creating amazing models, including 3D printed text, a warship model, a robot platform, windup toys, and arcade-inspired alien invaders. You'll learn about the different types of personal 3D printers and how they work; from the MakerBot to the RepRap printers like the Huxley and Mendel, as well as the whiteAnt CNC featured in the Apress book Printing in Plastic. You'll discover how easy it is to find and design 3D models using web-based 3D modeling, and even how to create a 3D model from a 2D image. After learning the basics, this book will walk you through building multi-part models with a steampunk warship project, working with meshes to build your own action heroes, and creating an autonomous robot chassis. Finally, you'll find even more bonus projects to build, including wind-up walkers, faceted vases for the home, and a handful of useful upgrades to modify and improve your 3D printer.